Visualization of Rectified Sine Waves and Triggering Angles on Thyristor Using Geogebra - Suwarno, Djoko Untoro (Proceeding International Conference on Mathematics and Learning Research, 2021)
GeoGebra is a tool that is widely used among academics to solve mathematical problems. GeoGebra can be visually generated in the form of graphs and computational results easily and quickly. In the field of electronic power, there is a problem with directed waves and waves triggered by a certain angle on the device thyristor. This paper will be discussed about visualization of rectified sine waveforms, triggering angles as well as integral values of directional waves in thyristor and three-phase source animation. With the GeoGebra tool, students can understand mathematical equations and make wave visualization on electronic power.